(untitled) (Psychology Travelogs, 2025)
The article highlights the theoretical foundations of the study of socio-psychological adaptation of university students and their learning motivation. The structure of the socio-psychological adaptation of the individual is revealed, a description of the educational and professional activities of the university student, the system of motives for learning activities is provided. The main features and conditions of the socio-psychological adaptation of the personality of a university student are reflected. The empirical study reveals differences in the indicators of socio-psychological adaptation and motives of learning activities of university students. The empirical study found that educational and professional activities are motivated by various motives: social, communicative, professional, educational, etc. The conditions for successful adaptation of university students are: formation of an adequate understanding of the chosen profession; assistance in understanding the social significance of the profession and instilling love for it; formation of adequate self-esteem; increasing volitional activity; conducting psychological and pedagogical diagnostics of the adaptation process; mastering methods of mental self-regulation; activities of the psychological service of the university, since the adaptation process is not fully possible without professional psychological support. For successful social and psychological adaptation, the most important are social and communicative motives, professional and educational and cognitive motives. The relationship between these motives and socio-psychological adaptation is due to the fact that certain processes take place in the student group: the manifestation of interest in educational and professional activities, the formation of interpersonal relationships, a system of attitudes and values, and, in general, the formation of a professional specialist. for successful socio-psychological adaptation, the most important are social and communicative motives, professional and educational and cognitive motives.